2018
DOI: 10.1080/10810730.2018.1500659
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Media Literacy Intervention for Indoor Tanning Prevention

Abstract: Indoor tanning leads to melanoma, the fifth most common cancer in the USA. The highest rate of indoor tanning is among young women whose exposure to tanned images in the media is linked to protanning attitudes. This study evaluated the efficacy of a media literacy intervention for reducing young women's indoor tanning. Intervention participants analyzed the content and functions of the media influencing protanning attitudes and produced counter-messages to help themselves and peers resist harmful media effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
7
1
Order By: Relevance
“…For example, providing youth with creative ways to participate in health campaigns could be a way to channel their self-expression motivation. A recent study found that production of digital counter messages by youth helped reduce risk behavior among them [56].…”
Section: Discussionmentioning
confidence: 99%
“…For example, providing youth with creative ways to participate in health campaigns could be a way to channel their self-expression motivation. A recent study found that production of digital counter messages by youth helped reduce risk behavior among them [56].…”
Section: Discussionmentioning
confidence: 99%
“…We employed this approach because the data were inconsistent with the assumptions of a Poisson or a negative binomial distribution. Similar to the Cho et al (2018) sample comprised of sorority women, this sample of college women reported two primary responses at the follow-ups: A substantial number of participants reported zero IT behavior, while a subgroup reported ten or more times IT per month. Therefore, consistent with Cho et al (2018), we transformed the number of occurrences of IT behavior to a binary response, where 1 indicated the occurrence of IT and 0 indicated no IT.…”
Section: Behaviormentioning
confidence: 99%
“…As indicated above, this web-based intervention adapted the content of a previously developed and evaluated MLI (Cho et al, 2018). Because the prior intervention was delivered in-person in the field at sorority houses, the format was transformed to fit the web platform.…”
Section: The Interventionmentioning
confidence: 99%
See 2 more Smart Citations